Intervening factors of patient safety culture in primary health care (Revista Contexto & Saúde, 2020)
Introduction: Identify the factors that interfere in the culture of patient safety in primary health care.Method: Integrative review was performed in the LILACS, PubMed, WoS and Scopus databases in August 2017. The level of evidence classification was used to perform a critical evaluation of the primary studies. There were 16 scientific productions.Results: The factors that interfere in the culture of patient safety in primary health care are conditions related to permanent education, communication, working conditions and leadership.Conclusions: The scientific evidence shows that some factors interfere positively, others negatively affect the culture of patient safety in primary health care and should be used in order to effect health actions for users.
Keywords: Patient safety; Primary health care; Risk management; Organizational culture.